2018
DOI: 10.18662/rrem/55
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Emigration Enablers of the Romanian Students in Theology

Abstract: The main purpose of this article is to describe and validate/test a set of hypothetical traits of the theology students from two important Romanian universities regarding their migration attitudes after graduation. The study is based on a consistent questionnaire survey, both in terms of architecture of variables and number of complete responses. After cleaning, processing and doing all the required derivations on the original data, statistical analysis methods have been applied. The results have brought solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The eff ect of the core variable is signifi cant and robust across all six scenarios (Table 2, These results, which indicate that students inclined more to place a great emphasis on the recognition of their personal value are more likely to migrate, validate the fi rst hypothesis, H1. These fi ndings are consistent with the ones from another study focused on a diff erent target population represented by students in Theology (Plopeanu et al, 2018).…”
Section: Predictors For Students' Migration Intentionsupporting
confidence: 91%
“…The eff ect of the core variable is signifi cant and robust across all six scenarios (Table 2, These results, which indicate that students inclined more to place a great emphasis on the recognition of their personal value are more likely to migrate, validate the fi rst hypothesis, H1. These fi ndings are consistent with the ones from another study focused on a diff erent target population represented by students in Theology (Plopeanu et al, 2018).…”
Section: Predictors For Students' Migration Intentionsupporting
confidence: 91%
“…Yes/No/I do not know", from which we retained (variable clear_eq_migrWEur_pers_val_recog) only the clear conviction regarding this equivalence ("Yes" coded as 1, "No" and "I do not know" as 0). This variable's overwhelming influence, explainable by admitting the holistic nature of the corresponding question above, is also proven by a study on the migration enablers of Romanian students in theology [66] based on four hundred distinct responses. This strong influence is in line with an explanation offered by neoclassical macroeconomics, and mentioned in the review of Massey et al (1993), by successfully confirming the differences between the migration patterns of skilled workers compared to those of unqualified ones [67].…”
Section: Methodsmentioning
confidence: 87%
“…Moreover, we have previously conducted two research studies focused on migration intentions among Romanian students. The first one analyzes the migration enablers of students in theology [69] based on 400 distinct responses from two universities from Iasi and Sibiu. The corresponding results confirmed that the personal value recognition is also their main trigger for migration intentions.…”
Section: Literature Reviewmentioning
confidence: 99%